COVID-19: could CT provide the best population level biomarker? Incidental COVID-19 in major trauma patients suggests higher than predicted rates of infection in London. Issue 1 (January 2021) - Adam, E.J.; Grubnic, S.; Jacob, T.M.; Patel, J.H.; Blanks, R.
Abstract : AIM: To evaluate incidental findings in major trauma patients, and to explore whether computed tomography (CT) could be used to assess prevalence and estimate disease spread in the general population. MATERIALS AND METHODS: The study population included all patients admitted following major trauma between 1 January 2020 and 30 April 2020 with CT including the lungs ( n= 523). Major trauma patients admitted pre-COVID-19 from 1–31 January and 1–31 March 2019 comprised a control group ( n= 252). The assessing radiologists, blinded to the time period, used double reading with consensus to determine if the patient had CT signs of COVID-19. Lung appearances were classified as no evidence of COVID-19; minor signs; or major signs. The proportion of patients with incidental COVID-19 changes was recorded over the study period, and the percentage of the population who had been affected by COVID-19 by the end of April 2020 estimated. RESULTS: CT appearances consistent with COVID-19 began to exceed a background pre-COVID rate in the second week of February and did not decline until 2 weeks after lockdown. By the end of April 2020, approximately 45% of the population had been infected. CONCLUSIONS: CT of major trauma patients can be used to monitor the spread of COVID-19. This novel technique could be used retrospectively or prospectively anywhere where trauma scans are available, to monitor the disease in the local population. Highlights: It is not known how many people have had Covid-19 since many will be asymptomatic. Major trauma patients are an unselected group of the general population. Unsuspected cases emerged in early February, and decreased 2 weeks post lockdown. By the end of April we estimate 45.4% of the London population had been infected. This technique can track the pandemic and provide early warning of surges.